2006
DOI: 10.18388/abp.2006_3346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA damage in white blood cells of healthy human volunteers using the alkaline comet assay and the chromosome aberration test.

Abstract: The present study was undertaken to contribute to the characterization of the degree of variability in baseline damage in white blood cells from control population, and to investigate how this variability is associated with external and internal factors. Altogether 170 healthy volunteers, randomly selected from the general population of the Republic of Croatia, participated in the study. Two sensitive tests: the alkaline comet assay and the chromosome aberration test were applied to study the background levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…A systematic review of the literature published up to 2005 did not show a difference between levels of DNA strand breaks, EndoIII-and Fpg-sensitive sites in WBCs between women and men [16]. This is in agreement with several more recent studies that have shown no or equivocal difference between sexes in studies using multivariate analysis [21,23,25,26,28,[31][32][33][34]. In fact, only a few studies have shown sex-differences in multivariate analysis; these reported a higher level of DNA strand breaks in women [35] or a higher level in men [27].…”
Section: Intrinsic and Non-modifiable Factorssupporting
confidence: 86%
See 1 more Smart Citation
“…A systematic review of the literature published up to 2005 did not show a difference between levels of DNA strand breaks, EndoIII-and Fpg-sensitive sites in WBCs between women and men [16]. This is in agreement with several more recent studies that have shown no or equivocal difference between sexes in studies using multivariate analysis [21,23,25,26,28,[31][32][33][34]. In fact, only a few studies have shown sex-differences in multivariate analysis; these reported a higher level of DNA strand breaks in women [35] or a higher level in men [27].…”
Section: Intrinsic and Non-modifiable Factorssupporting
confidence: 86%
“…A meta-analysis of studies published up to 2005 has shown a positive association between age and levels of DNA strand breaks in WBCs in studies that had used %DNA in tail and visual classification as comet assay descriptors, whereas there was no difference in levels of Endonuclease III (EndoIII)-and Formamidopyrimidine DNA glycosylase (Fpg)-sensitive sites [16]. More recent studies, which specifically have assessed age-differences in levels of DNA strand breaks, have reported positive [17][18][19][20][21][22][23], null [24][25][26][27][28], or negative associations [29]. The discrepancy between studies may be related to multiple factors such as the age span, type of WBCs, analysis of fresh or frozen sample and the statistical analysis.…”
Section: Intrinsic and Non-modifiable Factorsmentioning
confidence: 99%
“…The results obtained in this study showed higher levels of baseline genome damage in leukocytes of patients with carcinoma of the oropharynx than in Croatian general population (22). In some, the DNA damage measured by the alkaline comet assay was comparable to background values of the healthy population, but in others it was notably higher, even 2-fold higher than the normal values (23). Increased endogenous DNA/chromosome damage could be to some extent related to diagnostic exposures.…”
Section: Discussionmentioning
confidence: 41%
“…Active smokers posses higher level of CAs than the passive smokers 38 . Smoking habit as an imperative part that induces the significant alterations in the genomic material 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The important risk factor that induces alterations in genetic material is found to be the consumption of tobacco products 8,9 . Tobacco smoking is the causative agent for cancer of the lung, larynx, oral cavity, bladder, pancreas, cervix, kidney, stomach, blood, liver, colon and rectum, and esophagus and also induces the risk of diabetes and rheumatoid arthritis 10 .…”
Section: Introductionmentioning
confidence: 99%